2022
DOI: 10.48550/arxiv.2201.04552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generating enhanced primordial GWs during inflation with intermittent violation of NEC and diminishment of GW propagating speed

Yong Cai,
Yun-Song Piao

Abstract: We investigate both the null energy condition (NEC) violating scenario and the c T -diminishing scenario for generating enhanced power spectrum of primordial gravitational waves (GWs) during inflation, where c T is the propagating speed of primordial GWs. Both of these two scenarios can be realized stably with theories beyond Horndeski, hence can be uniformly implemented within the framework of the effective field theory. We calculate the power spectrum of primordial GWs by assuming that the inflationary Unive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…The violation of the NEC has profound implications for the generation of primordial GWs in the early Universe. It has been shown that NEC violation can result in a notable JCAP06(2024)028 amplification of the primordial tensor power spectrum at certain scales [40,41]. This amplification manifests as a blue tilt in the tensor power spectrum, indicating an enhanced production of high-frequency GWs.…”
Section: Introductionmentioning
confidence: 99%
“…The violation of the NEC has profound implications for the generation of primordial GWs in the early Universe. It has been shown that NEC violation can result in a notable JCAP06(2024)028 amplification of the primordial tensor power spectrum at certain scales [40,41]. This amplification manifests as a blue tilt in the tensor power spectrum, indicating an enhanced production of high-frequency GWs.…”
Section: Introductionmentioning
confidence: 99%